Association of social capital with self-perceived eHealth literacy among community-dwelling older people: Age and gender differences - Cao, Chenglin; Cao, Wenwen; Zheng, Xin; Ji, Kai; Wu, Yunwei; Hu, Zhi; Chen, Ruoling; Bai, Zhongliang (Frontiers in Public Health, 2023)
Background Studies have confirmed that social factors, including social capital and eHealth literacy, are important in later life. Currently, few studies are available for determining the relationship between social capital and eHealth literacy, and whether such a relationship exists among older people and there are age and gender differences in the relationship remain unclear. Consequently, this study aimed to investigate the association between social capital and eHealth literacy, specifically examing its variations in age and gender. Methods A cross-sectional study of 4,257 residents aged ≥ 60 years and dwelling in the community was conducted across four cities in China. A structured questionnaire was used to collect data on general characteristics, socioeconomic status, social capital, and eHealth literacy. Generalized linear models were employed to assess these associations. Results There were 4,218 respondents (age 71.9 ± 7.2 years; 64.8% women). Overall, social participation, social connection, trust, cohesion, and reciprocity were all statistically associated with eHealth literacy (p < 0.05), while such an association was not observed for social support (p > 0.05). Specifically, a higher level of social participation was associated with better eHealth literacy scores among participants aged 70–79 years (p < 0.001), and a higher level of social connection was associated with better eHealth literacy scores for those aged 60–69 and 70–79 years (p < 0.001). Meanwhile, no gender differences in the associations were found. Conclusion There is an association between social capital and eHealth literacy in older men and women. The association varis with age. The findings provide a reference for developing targeted measures to improve self-perceived eHealth literacy among older people. It is essential for achieving active and healthy aging and developing the knowledge and understanding of relevant theories, concepts, and evidence within the field of health and social capital.